MORTALITY ESTIMATES OF INDIAN RIBBON FISH TRICHIURUS LEPTURUS OFF MAHARASHTRA COAST - MOHITE, ASHISH; BIRADAR, R. S. (Journal of Indian Fisheries Association, 2016)
In view of its new found status in export market, ribbon fish resources need to be continusly monitored. Mortality, one of the important parameter is reported for the Indian ribbon fish Trichiurus lepturus Linnaeus in the present communication. The average annual instantaneous rate of total (Z), natural (M) and fishing mortality coefficient (F) were estimated as 2.66, 0. 77 and 1.89 respectively for the 1995 to 1997 period. The exploitation rate (U) and exploitation ratio (E) were estimated as 0.66 and 0.71 respectively, which is beyond the optimum Thursreduction in the fishing effort for this stock along the Maharashtra coast is necessary. Keywords : Mortality, Exploitation rate, Trichiurus lepturus.